A parent manual in teaching sex education to adolescents with mental retardation - Obnial, Irene Esguerra (2008)
This study on parent manual in teaching sex education to adolescents with mental retardation is a qualitative-descriptive research which sought to look into the needs of parents of adolescents with mental retardation (AMR) in imparting knowledge about sex education to their special children. The research samples consisted of 30 parents of adolescents with mental retardation attending a special school. Findings showed that parents agree that the responsibility for sex education should be shared between the home and the school. Religion may not be a factor in successful teaching of sex education. Recommendations were given in relation to parents, school, parent empowerment, training, and sex education curriculum for children with mental retardation.